Linguistic Fractionalization and Health Information in Sub-Saharan Africa - Gomes, Joseph Flavian (Published by Oxford University Press on behalf of the World Bank, 2021)
This paper explores the relationship between linguistic diversity and the stock of health information in society. Information is measured using individual-level knowledge about the oral rehydration product for treating children with diarrhea. Exploiting an individual woman-level dataset from the Demographic and Health Surveys for 14 sub-Saharan African countries combined with a novel high-resolution dataset on the spatial distribution of linguistic groups at a 1 km × 1 km level, this study shows that linguistic diversity has an inverted U-shaped relationship with the stock of information in society.